2019
DOI: 10.1590/0103-6440201902367
|View full text |Cite
|
Sign up to set email alerts
|

Determination of TNF-a Gene Polymorphisms on Skeletal Pattern in Class II Malocclusion

Abstract: Bone development and growth is a non-going, life-long process, varying greatly among individuals and much of this variation could be modulated by genetic factors. The purpose of this study was to evaluate the association between the polymorphisms in the TNF-a gene and skeletal class II malocclusion. Single nucleotide polymorphisms in TNF-a (rs1799724; rs1800629) gene were studied in 79 skeletal class II malocclusion and 102 skeletal class I malocclusion subjects from Straight Wire Group of Studies on Orthodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Single‐nucleotide polymorphisms (SNPs) are the most frequent variations in the human genome. SNPs in many genes were associated with different skeletal malocclusion phenotypes in different populations 15‐22 . Therefore, in this study we investigated SNPs in bone‐ and cartilage‐related genes in the aetiology of sagittal and vertical skeletal malocclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐nucleotide polymorphisms (SNPs) are the most frequent variations in the human genome. SNPs in many genes were associated with different skeletal malocclusion phenotypes in different populations 15‐22 . Therefore, in this study we investigated SNPs in bone‐ and cartilage‐related genes in the aetiology of sagittal and vertical skeletal malocclusions.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs in many genes were associated with different skeletal malocclusion phenotypes in different populations. [15][16][17][18][19][20][21][22] Therefore, in this study we investigated SNPs in bone-and cartilage-related genes in the aetiology of sagittal and vertical skeletal malocclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal Class II malocclusion etiology is considered to be multifactorial, in which both genetic and environmental factors play a role in its development. Maxillary and/or mandibular retrusion, also referred as retrognathism, are a common finding of genetic syndromes and conditions, for example, Pierre‐Robin, DiGeorge, Nager, Mobius syndromes (Jenzer & Schlam, 2020; Levy et al, 2019). There are no previous studies in the literature with ASMD individuals to compare these cephalometric findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies [84] have identified members of the TNF-α family and their receptors, as essential regulators of osteoclastogenesis. RANKL/RANK signaling regulates the formation of osteoclasts including bone modeling and remodeling.…”
Section: Genes Involved In Facial Bone Growthmentioning
confidence: 99%
“…Environmental factors play an especially important role in the development of a patient's morphofacial changes [84]. Among these factors there are functional etiological factors such as deleterious mouth habits and mouth breathing.…”
Section: F Environmental Factors Of Open Bitementioning
confidence: 99%